Question Number 215390 by MathematicalUser2357 last updated on 05/Jan/25 | ||
![]() | ||
$$\oint_{\gamma} {x}^{\mathrm{2}} {dx}\:\left[\gamma:\:{x}^{\mathrm{2}} +{y}^{\mathrm{2}} =\mathrm{1}\right] \\ $$ | ||
Answered by MrGaster last updated on 05/Jan/25 | ||
![]() | ||
$$\mathrm{solve}:\int_{\mathrm{0}} ^{\mathrm{2}\pi} \left(\mathrm{cos}\:{t}\right)^{\mathrm{2}} \left(−\mathrm{sin}\:{t}\right){dt}\left[\because{x}=\mathrm{cos}\:{t},{y}=\mathrm{sin}\:{t},{dx}=−\mathrm{sin}\:{t}\:{dt}\right] \\ $$$$\:\:\:−\:\:\int_{\mathrm{0}\:} ^{\mathrm{2}\pi} \mathrm{cos}^{\mathrm{2}} {t}\:\mathrm{sin}\:{t}\:{dt} \\ $$$$=−\left[\frac{\mathrm{cos}^{\mathrm{3}} {t}}{\mathrm{3}}\right]_{\mathrm{0}} ^{\mathrm{2}\pi} \\ $$$$=−\left(\frac{\mathrm{cos}^{\mathrm{3}} \left(\mathrm{2}\pi\right)}{\mathrm{3}}−\frac{\mathrm{cos}^{\mathrm{3}} \left(\mathrm{0}\right)}{\mathrm{3}}\right) \\ $$$$=−\left(\frac{\mathrm{1}}{\mathrm{3}}−\frac{\mathrm{1}}{\mathrm{3}}\right) \\ $$$$=\mathrm{0} \\ $$ | ||